Meningkatkan Kompetensi Administrasi Infrastruktur Jaringan VLAN Siswa SMK Melalui Website Pembelajaran Interaktif Berbasis PJBL - Arifandy, Luthfi; Prapanca, Aditya Prapanca (IT-Edu : Jurnal Information Technology and Education, 2025)
This research aims to design and develop a learning website using Project-Based Learning (PjBL) to enhance students' knowledge of Network Infrastructure Administration and VLAN configuration. The study involves students of class XI Computer and Network Engineering (TKJ) at SMK Ketintang Surabaya as the subjects. The research method chosen is Research and Development (R&D) using the ADDIE development model. This model is systematically designed through five stages: analysis, design, development, implementation, and evaluation. The results of the study show that the designed learning website has a high validation score, with media validation at 82.5%, material validation at 80%, pretest-posttest validation at 81.82%, and lesson plan (RPP) validation at 80%. The Shapiro-Wilk normality test results indicate that the significance values for the pretest, posttest, and project are 0.093, 0.071, and 0.353, respectively. Therefore, it can be concluded that the data is normally distributed. The paired t-test yields a two-tailed significance value of 0.000, indicating a significant influence on the improvement of students' skills after using the learning website. In conclusion, the PjBL-based learning website significantly contributes to enhancing the competencies of class XI TKJ students in the subject of Network Infrastructure Administration and their ability to configure VLANs.